Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1016/j.pcad.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Personal Activity Intelligence (PAI), Sedentary Behavior and Cardiovascular Risk Factor Clustering – the HUNT Study

Abstract: Prolonged sedentary behavior (SB) positively associates with clustering of risk factors for cardiovascular disease (CVD). The recently developed metric for physical activity (PA) tracking called Personal Activity Intelligence (PAI) takes into account age, sex, resting and maximum heart rate, and a score of ≥100 weekly PAI has been shown to reduce the risk of premature CVD death in healthy as well as individuals with known CVD risk factors, regardless of whether or not the current PA recommendations were met. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…35 Interestingly, only 40 minutes of high-intensity PA (w85% of the heart rate reserve) is needed to obtain 100 PAI. 16 When it comes to meeting the PA recommendations, one can perform either 150 minutes of moderateintensity PA or half as much (75 minutes) high-intensity PA. 6 A PAI score of 100 can, therefore, be earned by performing 35 minutes less PA than is currently recommended.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…35 Interestingly, only 40 minutes of high-intensity PA (w85% of the heart rate reserve) is needed to obtain 100 PAI. 16 When it comes to meeting the PA recommendations, one can perform either 150 minutes of moderateintensity PA or half as much (75 minutes) high-intensity PA. 6 A PAI score of 100 can, therefore, be earned by performing 35 minutes less PA than is currently recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The 3 intensity options correspond to 44%, 73%, and 83% of heart rate reserve. 15 According to the PAI algorithm previously described elsewhere, 15,16 we combined the exercise volumes with the reported exercise intensities by the use of heart rate reserves to estimate a weekly PAI score. Similarly, we combined frequency and duration of PA with the reported intensities to estimate whether participants were following contemporary PA recommendations.…”
Section: Pai and Pa Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the use of HR monitoring to provide feedback to participants and exercise specialists has a number of advantages over other technologies, such as pedometers and accelerometers. Heart rate is the most accurate way to track the body's adaptive response to exercise training, providing objective personalized data that account for age and fitness level (Zisko et al., ). Heart rate also reflects exercise intensity regardless of the type of exercise performed (Zisko et al., ).…”
Section: Benefits Of Home‐hit In People With Type 1 Diabetesmentioning
confidence: 99%
“…In many studies, those with moderate and high levels of CRF but with potent CVD risk factors have lower CVD morbidity and mortality than do those without these risk factors but who have low levels of CRF. Although high levels of physical activity (PA) have also provided substantial protection against CVD and mortality, 1-3 most studies have found that CRF is a much more powerful predictor of risk than is PA. 4,5 Certainly, however, moderate to high levels of PA, especially PA that is high-intensity or increases heart rate, [6][7][8] are generally needed to increase levels of CRF, but there are also inherited and genetic non-PA components of CRF. 1 In the current issue of Mayo Clinic Proceedings, 2 articles highlight the importance of CRF on subsequent CVD and mortality risk.…”
mentioning
confidence: 99%